FABRICATION OF THERMAL BIO-INSULATOR FROM OIL PALM TRUNK FIBER: ANALYSIS OF THERMAL, PHYSICAL AND MECHANICAL PROPERTIES - Yana, Debi; Husna, Ropiqotul; Kusmawati, Intan; Ginting, Delovita; Syahputra, Romi Fadli; Taer, Erman (Universitas Mataram, 2024)
The majority of air conditioning systems, including both cooling and heating systems, consume a significant amount of electrical energy as a result of their high electrical consumption and prolonged periods of operation. The use of thermal insulation materials in the building can help conserve electrical energy used for room conditioning systems. Natural fibers are used as an alternative in the production of thermal insulation, which is commonly referred to as bio-insulators. The utilization of oil palm trunk (OPT) fiber as the primary material for thermal insulation shows promise. This study aims to determine the specific attributes of OPT fiberboard that make it suitable for use as a thermal bio-insulator. The features examined encompass physical, mechanical, thermal, and fire-resistant attributes. The OPT fiber underwent a treatment process involving boiling at a temperature of 80â„ƒ for a duration of 30 minutes. The fiberboard is manufactured using epoxy adhesive and calcium carbonate additive, and then printed using the hand lay-up process and cold-compaction technique. The physical characteristics of fiberboard indicate that there is a direct relationship between its density and water absorption.Â Testing revealed that fiberboard has a low thermal conductivityÂ andÂ high heat capacity value. By including calcium carbonate, the burning time of the fiberboard was tested and seen to decrease, indicating a delay in the fiberboard burning process, as evidenced by the extended flame suppression time. The density of OPT fiberboard varies between 0.48 and 0.70 gr/cm3. The absorbency of water is inversely related to its density. Water absorption capacity generally rises with decreased density. The obtained heat capacity value is 1.28-2.38 Jâ„(gâ„ƒ). The mechanical value ranges from 1.00 to 3.55 MPa. The incorporation of calcium carbonate significantly impacts the thermal and mechanical characteristics of the fiberboard. The produced OPT fiberboard satisfies the requirements for good thermal, physical, and mechanical characteristics, making it a suitable bio-insulation material for buildings.